Aspectos da alimentação do pacu adulto, Colossoma mitrei (Berg, 1895) (Pisces, Characidae), no Pantanal de Mato Grosso - Silva, Antônia José da (1985)
The feeding of “pacu”, Colossoma mitrei (Berg, 1895) in the Pantanal of Mato Grosso, was investigated in the months of February and March 1977 and in the period between February 1981 and January 1982. Stomach fullness and diet composition in this species were directly related to the variation of the water levels in the region and the availability of food in the different biotopes studied. The stomachs contained both plant and animal food. The predomination of plant items in the diet of this species characterized it as being mainly herbivorus, although its diet did include secondary items such as fish, crustaceans and occasional mollusks. Fruits and seeds were the most important items among the available food sources in the diet of C. mitrei and were utilized in both flooded and receding water periods. How the clearing of land at the headwaters of the river and in flooded areas threatens the survíval of this species is discussed.